Increased enzymatic activity of acetylcholinesterase indicates the severity of the sterile inflammation and predicts patient outcome following traumatic injury - Živković, Aleksandar; Paul, Georgina M.; Hofer, Stefan; Schmidt, Karsten; Brenner, Thorsten; Weigand, Markus A.; Decker, Sebastian (Biomolecules, 2023)
Traumatic injury induces sterile inflammation, an immune response often associated with severe organ dysfunction. The cholinergic system acts as an anti-inflammatory in injured patients. Acetylcholinesterase (AChE), an enzyme responsible for the hydrolysis of acetylcholine, plays an essential role in controlling cholinergic activity. We hypothesized that a change in the AChE activity might indicate the severity of the traumatic injury. This study included 82 injured patients with an Injury Severity Score (ISS) of 4 or above and 40 individuals without injuries. Bedside-measured AChE was obtained on hospital arrival, followed by a second measurement 4-12 h later. C-reactive protein (CRP), white blood cell count (WBCC), and Sequential Organ Failure Assessment (SOFA) score were simultaneously collected. Injured patients showed an early and sustained increase in AChE activity. CRP remained unaffected at hospital admission and increased subsequently. Initially elevated WBCC recovered 4-12 h later. AChE activity directly correlated with the ISS and SOFA scores and predicted the length of ICU stay when measured at hospital admission. An early and sustained increase in AChE activity correlated with the injury severity and could predict the length of ICU stay in injured patients, rendering this assay a complementary diagnostic and prognostic tool at the hand of the attending clinician in the emergency unit.